1982
DOI: 10.1002/bjs.1800690418
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease in the older patient

Abstract: This paper presents a review of 64 patients in whom the first symptoms of inflammatory bowel disease occurred after the age of 60 years. Inflammatory bowel disease in older patients affects the large bowel much more commonly than the small bowel. The commonest variant is disease localized in the rectum and distal colon, and many of these patients have Crohn's disease (14 out of 28 patients). In 19 patients with localized left-sided colitis it was difficult to distinguish ischaemic colitis, acute diverticulitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…A small decrease in the incidence rate with advancing age in both males and females is consistent with previous data, most notably the European collaborative study [30]. Whereas low female-tomale ratios have been reported in studies of younger CD patients, there were twice as many women as men in our population and in most other studies of CD patients older than 60 years [3][4][5]10,11,13,[16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A small decrease in the incidence rate with advancing age in both males and females is consistent with previous data, most notably the European collaborative study [30]. Whereas low female-tomale ratios have been reported in studies of younger CD patients, there were twice as many women as men in our population and in most other studies of CD patients older than 60 years [3][4][5]10,11,13,[16][17][18][19][20].…”
Section: Discussionsupporting
confidence: 92%
“…A higher rate of distal colonic involvement has often been described in older CD patients, either at presentation [3,29] or during follow-up [11,14,17]. Although few studies found that up to 50% of older CD patients had disease confined to the small bowel [4,10], most studies noted a higher prevalence of colonic disease in the older age groups; thus, the disease was confined to the colon in 27-92% of older patients as compared to only 5-32% of younger patients [3][4][5][14][15][16][17].…”
Section: Symptoms Of CD In Elderly Patients Were Similar Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it should be noted that a previous report indicated that older male patients with UC treated with colectomy were susceptible to poor outcomes after surgery. 18 In our study, massive hemorrhage relatively frequently caused colectomy in patients with a disease duration of less than five years (Table 4), and in patients with an onset at younger than aged 40 years (data not shown). Although a previous report indicated that massive hemorrhage because of UC occurred preferentially in younger patients, 19 this report was based on data collected before 1986, and recent reports have scarcely referred to this issue.…”
Section: Discussionmentioning
confidence: 54%
“…The course of Crohn's disease in these two groups (early onset and late onset) appears to differ. Late-onset patients have more colonic involvement and less family history of inflammatory bowel disease (IBD) than early-onset patients [3,5]. Some studies have suggested that early-onset Crohn's disease has a more aggressive course than late-onset disease [3,6,7], whereas others refute this contention [8].…”
Section: Introductionmentioning
confidence: 95%